2002
DOI: 10.1098/rspb.2002.2180
|View full text |Cite
|
Sign up to set email alerts
|

Recent experience modulates forebrain gene–expression in response to mate–choice cues in European starlings

Abstract: Mate-choice decisions can be experience dependent, but we know little about how the brain processes stimuli that release such decisions. Female European starlings (Sturnus vulgaris) prefer males with longbout songs over males with short-bout songs, and show higher expression of the immediate early gene (IEG) ZENK in the auditory forebrain when exposed to long-bout songs than when exposed to shortbout songs. We exposed female starlings to a short-day photoperiod for one of three durations and then, on an increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 42 publications
(36 reference statements)
4
107
1
Order By: Relevance
“…Alternatively, one toral region may provide all acoustic processing used for mating decisions, but the distinct functions of the other regions (e.g., sound localization) yield egr-1 response patterns conducive to statistical, but not behavioral, stimulus discrimination. In this latter case, forebrain targets of the toral region responsible for call processing may have significant egr-1 biases both for conspecific calls and for whinechucks over whines, although no midbrain region showed such biases, as has been shown in a songbird (Sockman et al, 2002). Further experiments are required to determine whether the auditory midbrain regions have different analytic or integrative functions, and how these roles relate to thalamic specializations (Hall and Feng, 1987) and mating call detection in other brain regions.…”
Section: Parallel Processing Of Complex Acoustic Stimulimentioning
confidence: 93%
See 1 more Smart Citation
“…Alternatively, one toral region may provide all acoustic processing used for mating decisions, but the distinct functions of the other regions (e.g., sound localization) yield egr-1 response patterns conducive to statistical, but not behavioral, stimulus discrimination. In this latter case, forebrain targets of the toral region responsible for call processing may have significant egr-1 biases both for conspecific calls and for whinechucks over whines, although no midbrain region showed such biases, as has been shown in a songbird (Sockman et al, 2002). Further experiments are required to determine whether the auditory midbrain regions have different analytic or integrative functions, and how these roles relate to thalamic specializations (Hall and Feng, 1987) and mating call detection in other brain regions.…”
Section: Parallel Processing Of Complex Acoustic Stimulimentioning
confidence: 93%
“…We chose egr-1 quantification as our measure of neural activity based on its previous effectiveness in measuring auditory biases for acoustic communication signals (Mello et al, 1992;Gentner et al, 2001;Sockman et al, 2002;Maney et al, 2003). Neuronal egr-1 expression is regulated by synaptic activity and is linked to membrane depolarization through multiple second messenger cascades (Murphy et al, 1991;Whitmarsh et al, 1995;Treisman, 1996;Harada et al, 2001;Sweatt, 2001;Bozon et al, 2003;Buchwalter et al, 2004;Cheng and Clayton, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…ovulation order of the first-breeding attempt) and withingeneration fine-tuning of an induced effect (e.g. in relation to familiarity with mate, food fluctuations) are frequently documented (Cheng 1986;Yoo et al 1986;Sockman et al 2002;Pfaff et al 2004) and commonly attributed to complexity and redundancy of endocrine reproductive systems where the same hormonal mechanisms are involved in the assessment of environmental variation and oocyte proliferation and ovulation (e.g. Ball & Balthazart 2008).…”
Section: Evidence For the Baldwin Effect's Processes (A) Environmentamentioning
confidence: 99%
“…Nevertheless, female zebra finches can learn to recognize songs to which they have been exposed, and they develop a preference for these songs (Riebel, 2000;Riebel et al, 2002). Several studies have shown that both the NCM and the CMHV are involved in processing conspecific songs in female songbirds (Chew et al, 1996;MacDougall-Shackleton et al, 1998;Duffy et al, 1999;Gentner et al, 2001;Bailey et al, 2002;Sockman et al, 2002;Bailey and Wade, 2003;Gentner and Margoliash, 2003;Grace et al, 2003;Maney et al, 2003;Phillmore et al, 2003), as well as in female budgerigars . Preliminary results from our own laboratory indicate that, in female zebra finches, the CMHV may be part of the neural representation of learned tutor song (Terpstra et al, 2001).…”
Section: The Role Of the Cmhv In Tutor Song Representationmentioning
confidence: 99%